2014
DOI: 10.3923/bj.2015.25.39
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vacuum-packaging on the Microbiological, Chemical, Textural and Sensory Changes of the Solar Rack Dried Sardines During Chill Storage

Abstract: Solar dried clupeid sardine fishery storage along the Kenyan coast has always been carried out unhygienically using gunny bags kept under ambient conditions. Shelf life changes of the vacuum-packaged solar rack dried sardines during chill storage were therefore examined, to determine the occurring microbiological, chemical, textural and sensory changes in the gunny bag (GBP), control air (CAP), experimental air (EAP) and Experimental Vacuum Packaged (EVP) samples. Pouches (size: 15×22 cm) made of 12 μ-polyeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
(40 reference statements)
2
2
0
Order By: Relevance
“…However, there was a slight increase in pH (6.2±0.01 -6.3±0.01) in VPSPs during storage of the product. This observation is in agreement with a related study carried out by Ochieng et al (2015) which involved monitoring the effects of vacuum packaging on the chemical properties of solar rack dried sardines during chill storage. The increase in pH reported in this study during storage of VPSP could be as a result of ammonia (volatile base compound) released by spoilage bacterial activities during storage of the product.…”
Section: Physicochemical Parameterssupporting
confidence: 92%
See 1 more Smart Citation
“…However, there was a slight increase in pH (6.2±0.01 -6.3±0.01) in VPSPs during storage of the product. This observation is in agreement with a related study carried out by Ochieng et al (2015) which involved monitoring the effects of vacuum packaging on the chemical properties of solar rack dried sardines during chill storage. The increase in pH reported in this study during storage of VPSP could be as a result of ammonia (volatile base compound) released by spoilage bacterial activities during storage of the product.…”
Section: Physicochemical Parameterssupporting
confidence: 92%
“…During storage of VPSP at ambient temperature (28±2°C), reduction in pH of the samples (pH 6.2) occurred at Week 4. The slight reduction in pH observed in this study was earlier reported by Ochieng et al (2015) from a related study. However, there was a slight increase in pH (6.2±0.01 -6.3±0.01) in VPSPs during storage of the product.…”
Section: Physicochemical Parameterssupporting
confidence: 88%
“…However, TVBN values of T1 sample was very near to the rejection limit at 6 month of storage. It has been reported that the lowest TVBN value (5.6 to 19.5 mg/100g) was recorded in vacuum-packaged dried sardine compared to the treated samples during 90 days of storage (Ochieng et al, 2015). Moringa water extract combined with vacuum packaging showed synergistic effect in reducing TVBN value, which reduces the bacterial number or the bacterial deamination property on non-protein nitrogenous compound due to the presence of phenolic compounds in moringa.…”
Section: Total Volatile Base Nitrogen (Tvbn)mentioning
confidence: 91%
“…The TVBN indicates the degree of spoilage of fishery product mainly composed of ammonia, primary, secondary and tertiary amines (Ochieng et al, 2015). TVBN value increased from 11.78 to 72.76 mg/100g, 10.78 to 49.29 mg/100g, 10.34 to 44.78 mg/100g, 10.24 to 43.74 mg/100g for the control, T1, T2, and T3 samples, respectively (Fig.…”
Section: Total Volatile Base Nitrogen (Tvbn)mentioning
confidence: 93%